Expression of Sobbing Humanity in Fiction of Rasheed Amjad - Muhammad Yousaf; Muhammad Afzal Butt (دریافت)
Rasheed Amjid is an awakened brain fiction writer. Reading his stories, one realizes that he is familiar with every vein of society like a pulse expert. He has told in his stories that Allah has sent man as a noble creature and has imposed responsibilities on him according to his status. But the rapid scientific progress has deprived man of his basic qualities. The spirit of self-sacrifice and service to human beings is disappearing. In this age of mechanization, all the schools are also producing a generation that is a conqueror of speech but has no character. All institutions have become a story of decline. The sighs, sobs and cries of the poor are being heard from all sides. This social decline has licked this seemingly beautiful society like a termite from within.  Rashid Amjid wants to rectify this situation. The lamentations of dead humanity written by Rasheed Amjid are covered in this article.